The Palgrave handbook of Britain and the Holocaust - Lawson, Tom (Palgrave Macmillan, 2020)
This handbook is the most comprehensive and up-to-date single volume on the history and memory of the Holocaust in Britain. It traces the complex relationship between Britain and the destruction of Europe?s Jews, from societal and political responses to persecution in the 1930s, through formal reactions to war and genocide, to works of representation and remembrance in post-war Britain. Through this process the handbook not only updates existing historiography of Britain and the Holocaust; it also adds new dimensions to our understanding by exploring the constant interface and interplay of history and memory. The chapters bring together internationally renowned academics and talented younger scholars. Collectively, they examine a raft of themes and issues concerning the actions of contemporaries to the Holocaust, and the responses of those who came ?after?. At a time when the Holocaust-related activity in Britain proceeds apace, the contributors to this handbook highlight the importance of rooting what we know and understand about Britain and the Holocaust in historical actuality. This, the volume suggests, is the only way to respond meaningfully to the challenges posed by the Holocaust and ensure that the memory of it has purpose